PEMBUATAN APLIKASI PENJUALAN BINATANG TERNAK BERBASIS ANDROID DI PETERNAKAN BEBEK ALFALAH DESA PADAULUN - COMPUTING INFORMATIKA; Iyus A muslimin; Denny Rusdianto (COMPUTING | Jurnal Informatika, 2022)
ABSTRACT: In line with the rapid development of this technology, business actors are increasingly encouraged to use technology as a weapon to stay afloat and win the competition that is getting tougher and harder every day. Unlike the Bebek Alfalah livestock business which is still not effective and efficient because the buying and selling process is still carried out directly on the spot because the number of sales transactions is still relatively low because many businesses that are still doing promotions and sales still use brochures or billboards, so the author decided to design an e- commerce application for the livestock marketing business which can later facilitate the Alfalah Duck farm in conducting sales and promotions of duck and meat livestock that can be expected to make it easier for potential buyers to get information about the farm and duck meat. Then the design is implemented by using Laravel to build applications to be managed by admins and using fluter to build applications for use by customers in ordering products. Farm animal sales applications created using Laravel and fluter are ready to run as they function.